2012
DOI: 10.2967/jnmt.111.094268
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring Safe and Quality Medication Use in Nuclear Medicine: A Collaborative Team Achieves Compliance with Medication Management Standards

Abstract: As hospital nuclear medicine departments were established in the 1960s and 1970s, each department developed detailed policies and procedures to meet the specialized and specific handling requirements of radiopharmaceuticals. In many health systems, radiopharmaceuticals are still unique as the only drugs not under the control of the health system pharmacy; however, the clear trend-and now an accreditation requirement-is to merge radiopharmaceutical management with the overall health system medication management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…also indicated that collaborative efforts between pharmacy and nuclear medicine teams help achieve compliance and improve quality control systems and safe use of radiopharmaceuticals. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…also indicated that collaborative efforts between pharmacy and nuclear medicine teams help achieve compliance and improve quality control systems and safe use of radiopharmaceuticals. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, in the Philippines, there is increasing use of radiopharmaceuticals. However, only a few hospitals have encouraged the inclusion of pharmacists in the nuclear pharmacy unit (Bautista & San Luis Jr, 2016). Beach et al (2012) advocated the inclusion of radiopharmacists in the nuclear medicine team to provide appropriate and adequate pharmaceutical care.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few hospitals have encouraged the inclusion of pharmacists in the nuclear pharmacy unit (Bautista & San Luis Jr, 2016). Beach et al (2012) advocated the inclusion of radiopharmacists in the nuclear medicine team to provide appropriate and adequate pharmaceutical care. The International Atomic Energy Agency had reported an acute shortage of radiopharmacists resulting from the absence of pharmacists with adequate radiopharmacy training or certification (Agency, 2010).…”
Section: Introductionmentioning
confidence: 99%